A utilização de smartphones no acesso à informação científica por jovens estudantes : um estudo de caso - Fenerick, Gabriele Maris Pereira (2017)
Adapting constantly to new scenarios, society develops with great influence of technology. Smartphones, communication technology present in the various social layers, can contribute to the democratization of access to scientific information. Considering the social dimensions that this fact extends, it is understood that it is necessary to carry out studies that establish an association between the theoretical and practical perspectives that involve such questions. Therefore, the objective of this research is to investigate how smartphones effectively contribute to the access to scientific information by young students of the Álvaro Guião State School, located in the city of São Carlos, São Paulo. The justifications for conducting this research are based on the need to understand how these students currently contemplate aspects related to science. The proposed methodology is based on two aspects: 1) theoretical study through a bibliographical survey, comprising the themes: Scientific dissemination; Scientific information; Scientific communication by electronic means; And Information and Communication Technologies; 2) empirical study - developed based on experimental knowledge of young smartphone users. The data collection instrument used in this research was the questionnaire, applied to a group of young people, students of the third year of high school at the Álvaro Guião school, in the city of São Carlos. The results of the research demonstrated that despite different socioeconomic contexts and social environments among groups of students, there is a valorization of scientific information by the dominant cultural capital in the school environment that encourages them to access scientific dissemination in order to have sociability. It is concluded that the availability of open networks added to the increase in the number of young people who have smartphones, effectively contribute to the scientific dissemination and, consequently, to the access of these students to scientific information.